Discussion of Ability Cultivation of Computational Thinking in Course Teaching - Zhenrong Deng; Wenming Huang; Rongsheng Dong (2009 International Conference on Education Technology and Computer, 2009)
Computational thinking is taken for the fundamental skills for everyone, not just computer scientist, to learn and use. It remains to be explored in many aspects how to understand the essence of computational thinking and how cultivate the computational thinking ability of students. In the view of course teaching of computer science, this paper discusses the perception of the essence of computational thinking and presents a method for the cultivation of the computational thinking ability by using courses as carrier, and a case study of the course Data Structures and Algorithms.